Vincristine-induced peripheral neurotoxicity: A prospective cohort. (2nd January 2020) - Nama, Nassr; Barker, Mikaela K.; Kwan, Celia; Sabarre, Cheryl; Solimano, Veronica; Rankin, Anne; Raabe, Jennifer; Ross, Colin J.; Carleton, Bruce; Zwicker, Jill G.; Rassekh, Shahrad Rod
Abstract: Vincristine-induced peripheral neuropathy (VIPN) is a serious and pervasive problem, affecting 12–78% of pediatric patients, based on retrospective studies. The study objective was to prospectively collect a cohort of well-phenotyped patients receiving vincristine in order to accurately classify and grade their neurotoxicity. All children in British Columbia with leukemia or lymphoma requiring vincristine between 2013 and 2016 were approached for consent. Those recruited were assessed by occupational and physiotherapists at baseline, mid and endpoint of their treatment. Assessments included the Bruininks–Oseretsky Test of Motor Proficiency – 2nd ed. (BOT-2), strength, "Timed up and go" test and vibration sensibility. Seventy-two patients consented (age: 2.0–18.7 years). The majority were below average for age on one or more BOT-2 domains at midpoint ( N  = 32/45, 71%), which decreased by the endpoint ( N  = 19/41, 46%, p  = .049). Six patients showed severe VIPN throughout treatment ( N  = 6/53, 11%), defined as a BOT-2 score well below average. Muscle strength for wrist extension/flexion, anterior tibialis and peronei decreased significantly between baseline (Median = 5) and midpoint (Median = 4), with no significant change noted by endpoint. Most patients had normal vibration sensibility in lower ( N  = 30/60, 50%) and upper limbs ( N  = 26/38, 68%). In conclusion, with no differences between time points. VIPN is highly prevalent among patients with pediatric cancer, causing significant morbidity and functional deficits. Identification of risk factors would allow for resource appropriation to patients at higher risk, as well as potentially permitting dose escalation in patients with low toxicity to improve survival.